Global Models of Criminalistics and Forensic Science - V. Ya. Koldin; K. K. Seitenov; O. A. Krestovnikov (Теория и практика судебной экспертизы)
The paper looks at the world’s systems and models of criminalistics and forensic science. Comparison of the conceptual foundations and technological subsystems of forensic knowledge of the Austro-German, Roman and Anglo-Saxon schools (the concept of «Forensic Science») reveals an important pattern in the development of criminalistics and forensic science in Russia. The indicated vectors and prospects for further evolution of national criminalistics and forensic science point to a clear trend towards differentiation of specialized knowledge by branches, objects, methods and levels of investigation. The strengths and weaknesses of the western and Russian systems of forensic knowledge are demonstrated. Conclusions and recommendations are put forward regarding the modernization of both the structure and the theoretical and methodological framework of criminalistics and forensic science in Russia.